Increased Overjet as a Predictor of the Magnitude of Skeletal Class II Malocclusion Correction: A Retrospective Analysis of Early Treatment with the Manni Telescopic Herbst Appliance - Antonio Manni; Emma Gotti; Fabio Castellana; Giorgio Gastaldi; Mauro Cozzani; Andrea Boggio (Oral, 2025)
Background: Class II Division 1 malocclusion is often characterized by an increased overjet, which has traditionally been considered a negative predictor of aesthetic outcomes, treatment efficacy, and long-term stability. Although early two-phase treatment is generally perceived as less effective than a single-stage pubertal peak intervention, it may be beneficial in cases with concerns such as trauma risk or bullying. This study aimed to assess the relationship between initial overjet and sagittal correction (as measured by the ANB and WITS indices) to identify a threshold beyond which two-phase treatment might be more effective. Methods: A retrospective analysis was conducted on 58 patients (mean age: 9.01 years), all of whom were treated consecutively with the Manni Telescopic Herbst Appliance. Lateral cephalograms taken at the start (T0) and end (T1) of Herbst treatment were analyzed to evaluate changes in skeletal and dental parameters. Results: A significant positive correlation was found between higher initial overjet and increased skeletal sagittal correction. Specifically, for every 1 mm increase in overjet, there was a 0.65 mm reduction in the WITS index and a 0.30° decrease in the ANB angle (p < 0.01). These effects were more pronounced when the initial overjet exceeded 8.0 mm. Conclusions: The Manni Telescopic Herbst Appliance demonstrated enhanced skeletal correction in patients with larger initial overjet values, particularly when the overjet exceeded 8.0 mm. This suggests that early two-phase treatment may be especially beneficial in such cases.